2017
DOI: 10.1097/ico.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Antibiotic Susceptibility Profile, and Outcomes of Infectious Keratitis Caused by Stenotrophomonas maltophilia

Abstract: Purpose Stenotrophomonas maltophilia, an uncommon cause of infectious keratitis, is difficult to treat due to its resistance to multiple antibiotics. The purpose of this study is to describe the clinical features, antibiotic susceptibility profile, and outcomes of S. maltophilia keratitis. Methods A retrospective review of records from 1987–2014 identified 26 eyes of 26 patients who were treated at the Bascom Palmer Eye Institute for a S. maltophilia corneal ulcer. Clinical data was analyzed as to predisposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
17
2
Order By: Relevance
“…Yet, the actual clinical efficacy of trimethoprim-sulfamethoxazole against S. maltophilia as well as against A. xylosoxidans may be limited as its inhibitory quotient was low (0.70 and 0.92, respectively, table 2). In a retrospective review of the medical records of patients treated for S. maltophilia keratitis in our institute during a 30-year period, we found that this pathogen showed as high as 92% susceptibility rate to fluoroquinolones, represented by ciprofloxacin 21. However, in the current report susceptibility rate to ciprofloxacin was as low as 13.3%.…”
Section: Discussioncontrasting
confidence: 60%
“…Yet, the actual clinical efficacy of trimethoprim-sulfamethoxazole against S. maltophilia as well as against A. xylosoxidans may be limited as its inhibitory quotient was low (0.70 and 0.92, respectively, table 2). In a retrospective review of the medical records of patients treated for S. maltophilia keratitis in our institute during a 30-year period, we found that this pathogen showed as high as 92% susceptibility rate to fluoroquinolones, represented by ciprofloxacin 21. However, in the current report susceptibility rate to ciprofloxacin was as low as 13.3%.…”
Section: Discussioncontrasting
confidence: 60%
“…For instance, bone implants are always associated with risks of bacterial infection that leads to implant failure or, in critical cases, amputation or death of the patient [144,145]. In contact with the eye lens this process causes serious eye infections [146]. Other examples of fouling formation are in catheter-associated urinary tract infections [147,148], and dental implants cause periodontal diseases and gingivitis [144].…”
Section: Antimicrobial and Antifouling Polymers Based On Electricamentioning
confidence: 99%
“…87 Similarly, these bacteria are found in contact lens cases of patients with CIEs. [88][89][90][91][92][93][94][95][96] Although rare, these bacteria have been reported as causes of MK in contact lens wearers. 89,90,[95][96][97][98] Achromobacter xylosoxidans is known to be resistant to multiple antibiotics including aminoglycosides, most cephalosporins and have varying sensitivity to fluoroquinolones.…”
Section: Bacterial Keratitismentioning
confidence: 99%
“…[88][89][90][91][92][93][94][95][96] Although rare, these bacteria have been reported as causes of MK in contact lens wearers. 89,90,[95][96][97][98] Achromobacter xylosoxidans is known to be resistant to multiple antibiotics including aminoglycosides, most cephalosporins and have varying sensitivity to fluoroquinolones. 89,90 Strains from both Stenotrophomonas maltophilia and Delftia acidovorans can be multidrug resistant.…”
Section: Bacterial Keratitismentioning
confidence: 99%
See 1 more Smart Citation